Application of virtual manufacturing using FEM in distortion analysis for welding, welding-forming and Wire Arc Additive Manufacturing process / Keval Priapratama Prajadhiana - Prajadhiana, Keval Priapratama (2019)
This master research deals with the application of Virtual Manufacturing (VM) using Finite Element Method (FEM) on manufacturing processes which consist of welding, coupled welding to forming and Wire Arc Additive Manufacturing (WAAM) process. Deformation behaviour caused by the mentioned manufacturing processes are main concern for this research investigated by means of VM and experiments. A series of experiment was conducted in order to verify the result of simulation, whereby materials chosen for this study are low carbon steel and High Strength Low Alloy (HSLA) steel. The material properties taken from experiment, previous researches and software database were implemented into simulation in order to ensure a realistic resemblance. The simulation was carried out by utilizing thermo-mechanical FEM under consideration of non-linear isotropic hardening using specialized and commercial FEM software namely SIMUFACT and MSC Marc/Mentat.